P54 Formative test questions in neurology and neurosurgery. Issue 3 (14th February 2019) - Tallantyre, EC; Corns, R; Smith, PE; Thomson, S
Abstract : Objectives: To provide a formative educational test of knowledge that allows clinicians to measure themselves against their peers. Design: Annual Neurosurgery and Neurology knowledge tests, supported by the ABN & SBNS, have been available since 2014 (NSurg) and 2017 (Neurol). The NSurg test requires all candidates to participate over 3 days, answers are available after the test whereas the Neurol formative questions are available over 6 weeks, answers are available immediately. Subjects: There have been 821 first attempts at the formative questions; NSurg; 44, 63, 187, 143, 164 and Neurol; 74, 146. Candidates are mostly from UK (NSurg 92%, Neurol 69%) and mostly specialty trainees (NSurg 98%, Neurol 63%). Methods: The formative questions are delivered through the ebrain virtual learning platform, statistics are generated automatically. Proposed questions are written by candidates as 'payment' for doing the formative test. Results: Mean Cronbach's alpha was 87.3%. The mean score for the tests was 60.4% (Range 55.9%–77.9%). Feedback is voluntary: In 2018 17 feedback comments were received, 10 were unambiguously positive, 5 were mixed including criticism of one or more questions, 2 were judged to be neutral. Examples of feedback comments received this year included 'Comprehensive exam that covers a wide range of topics' and 'This is of great value'. Conclusions: This formative educational initiative has high internal consistency and solid feedback. Although set up differently, it is proving both valuable and popular in both specialties.